Os preceitos gerenciais para o desenvolvimento: a influência do Banco Mundial para a consolidação do gerencialismo no Brasil na década de 1990 - Carneiro, Adele de Toledo (2019)
The present study aims to understand the position of the World Bank in the face of the consolidation of managerial precepts in the Brazilian public administration. The research aims to contribute to the theory of development management analysis, that is, the theory of Administration and Development Management (Brinkerhoff and Coston, 1999; Thomas, 2000) from a perspective on Brazil until then, shy in studies on the management of the Third World (Cooke, 2004). The role of the World Bank in the work with the Brazilian government is based not only on the volume of loans dedicated to the implementation in the public sector of the country, but also on the role played in scientific and diplomatic arguments about the development of the nation. In this way, we intend to understand how, although little noticed by the characters of that period, the scenario of the time provided a cooperative action of regulatory agencies to intervene in a contextual way in development management to promote economic growth and overcoming problems of public infrastructure. The period of study is justified by the heightened information on managerialism with post-Cold War events and neoliberal influence, implying in the movement for the elaboration and implementation of the Management Reform in Brazil in 1995, in the first term of Fernando Henrique Cardoso. For the accomplishment of the research, the documentary methodology was used from the interpretative perspective under analysis of what was based as contextual element of the time. A total of more than 180 documents of the period elaborated by the World Bank on the situation in the country were used, as well as other official documents prepared by the Brazilian government in the 1990s. Interviews were conducted with representatives of the government technical staff of the FHC period, witnesses of the project of managerial reform in 1995, being used in the research in a complementary form to the documentary data. The analysis of the data reveals not only the performance of the World Bank in relation to development management, but also evidence of the understanding of the Brazilian history of public administration.